2011
DOI: 10.2202/1944-4079.1067
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Hazard Adjustments by Large and Small Organizations: Who is Doing the Talking and Who is Doing the Walking?

Abstract: Environmental hazards pose a considerable and genuine threat to the survival of organizations. However, organizations can increase their likelihood of survival by adopting various hazard adjustments. Prior studies on hazard adjustments have found a positive relationship between the adoption of hazard adjustments and organization size. However, no study on hazard adjustments has grouped hazard adjustments into active and passive and studied the relationship between active and passive hazard adjustments and orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…In Dahlhamer and D'Souza's (1997) studies using the data from Memphis/ Shelby County, Tennessee and Des Moines/Polk County, Iowa, the larger businesses were more likely to engage in preparedness activities than their small counterparts-size was the strongest predictor of preparedness among business organizations in both communities. More recent studies at the organizational level also found that organizational size is a strong positive determinant of disaster mitigation and preparedness in organizations (Sadiq 2010(Sadiq , 2011. These studies revealed consistently that the size of a company is a strong predictor of its disaster preparedness.…”
Section: Firm Sizementioning
confidence: 78%
“…In Dahlhamer and D'Souza's (1997) studies using the data from Memphis/ Shelby County, Tennessee and Des Moines/Polk County, Iowa, the larger businesses were more likely to engage in preparedness activities than their small counterparts-size was the strongest predictor of preparedness among business organizations in both communities. More recent studies at the organizational level also found that organizational size is a strong positive determinant of disaster mitigation and preparedness in organizations (Sadiq 2010(Sadiq , 2011. These studies revealed consistently that the size of a company is a strong predictor of its disaster preparedness.…”
Section: Firm Sizementioning
confidence: 78%
“…The importance of hazard adjustments in any community cannot be overemphasized because hazard adjustments can help to enhance community resilience to disasters (Sadiq 2011). …”
Section: The Relationship Between Disaster Information and Hazard Adjmentioning
confidence: 99%
“…Second, this study used perceived organizational preparedness, not actual preparedness measures adopted by organizations, as measures of preparedness. Although the latter may result in more accurate measures of organizational preparedness than the former, the use of perceptual measures is prevalent among scholars (e.g., Brody, Zahran, Vedlitz, & Grover, ; Chikoto, Sadiq, & Fordyce, ; Fowler et al, ; Poussin, Botzen, & Aerts, ; Sadiq, ; Sadiq & Weible, ). Despite raising more questions than answers, this study provides the basis for future organizational preparedness research on climate change‐related natural hazards.…”
Section: Discussionmentioning
confidence: 99%